Lateral geniculate lesions block circadian phase-shift responses to a benzodiazepine. - Johnson, R F (1988)
Several pharmacological treatments, including application of an excitatory neurotoxin to the lateral geniculate nucleus (LGN) and systemic administration of triazolam, a clinically effective benzodiazepine, can elicit large phase shifts in a circadian rhythm according to the time of administration. The hypothesis that the LGN might mediate the effect of triazolam on circadian clock function was tested. Bilateral lesions of the LGN, which destroyed the connection from the intergeniculate leaflet to the suprachiasmatic nucleus, blocked phase-shift responses to triazolam. The requirement of an intact LGN for triazolam to shift circadian phase suggests that the LGN may be a site through which stimuli gain access to the circadian clock to modulate rhythm phase and entrainment.